Temperatura colonial e tolerância térmica de melipona subnitida, uma espécie de abelha sem ferrão (Hymenoptera, Apidae, Meliponini), da caatinga - Ferreira, Noeide da Silva (2014)
In stingless bees (Hymenoptera, Apidae, Meliponini), so far, thermal tolerance and social thermoregulation have received little scientific interest. Yet, both these topics are fundamental to understand the evolution of sociality and of the adaptations of this bee group to their natural environment, thus contributing to the conservation and sustainable management of Meliponini species. Here, was analysed the natural thermal conditions in nests of Melipona subnitida in the Caatinga biome and investigated the thermal tolerance of workers bees of this bee species. The present study was performed at the Experimental Field Station Rafael Fernandes and at the Laboratory of Behavioural Ecology, both belonging to the Federal Brazilian University at Mossoro-RN. For our investigation of the mechanisms of thermoregulation, we used two nests of M. subnitida, the first being a wooden box commonly used in stingless bee-keeping containing an intact bee colony, the second an abandoned nest localized in a living tree. The latter nest was used to evaluate the level of thermic insulation provided in a natural nesting cavity. Temperature data were registered at different areas inside the nests using thermo-sensors connected to data-loggers. For the determination of the thermal tolerance of M. subnitida adults, groups of workers were kept at different temperatures inside BOD incubators, supplied with sugar water and, in some experimental groups, water. The temperature inside the nests closely followed the variations in ambient temperature. Even so, the temperature in the brood area was more stable than that of the other investigated thermal environments. During our study, the temperature in the brood area varied between 27-33°C, and reached maximum values of 4° above outside environmental temperature. Both the reduced thermal variation and the temperature increase above ambient temperature in the brood area point to some form of active thermoregulation in M. subnitida. Further, thermal oscillations inside the tree trunk were smaller compared to those registered in the outside environment. This indicates that the nesting cavity provides some form of thermal insulation, probably related to the thickness of the wood around the cavity. Concerning the thermal tolerance of workers of M. subnitida, we found mortality rates of 100% at temperatures above 42°C and below 0°C, indicating these temperatures as lethal for this stingless bee species. The thermal tolerance (50% mortality) of workers was between 5 and 40°C. The access to water during the experiments increased the thermal tolerance of workers exposed to high temperatures